2021
DOI: 10.3329/bjz.v49i1.53686
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Copy’s Frog Hydrophylax Leptoglossa Based on 16s rRNA Gene

Abstract: Copy’s frog, commonly observed in Bangladesh, is ecologically important for evergreen forest. Sample was collected from Satchari National park, Hobigonj, Sylhet. Attempts were made to combine morphological and molecular techniques for identification and analysis of evolutionary relation of Copy’s frog with anuran species. Morphological identification of Hydrophylax sp. was conducted based on distinguishing characteristics of the body and different body measurement parameter. The species was identified morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The intraspecific genetic diversion was 2.45% for 12S rRNA gene (Table 8). According to Chowdhury et al (2021) when Hydrophylax tytleri and H. leptoglossa from different countries were compared the intraspecific variation was found to be 1.29%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intraspecific genetic diversion was 2.45% for 12S rRNA gene (Table 8). According to Chowdhury et al (2021) when Hydrophylax tytleri and H. leptoglossa from different countries were compared the intraspecific variation was found to be 1.29%.…”
Section: Resultsmentioning
confidence: 99%
“…In case of 12S rRNA gene sequence, it was compared with F. iskandari (AB277287) and F. limnocharis (KU840479) and the polymorphic divergence calculated were 4.41% and 6.86% respectively (Table 8). Another research showed around 14% polymorphic divergence between H. leptoglossa and H. tytleri in case of 16S rRNA gene sequence (Chowdhury et al 2021). The sequence length was much shorter, which may have caused the higher polymorphic divergence.…”
Section: G -mentioning
confidence: 96%